(untitled) (Papeles, 2025)
Introduction: The aim of this article is to investigate the categories of field, capital, habitus and illusio, constitutive tools of Pierre Bourdieu’s constructivist structuralism, and to highlight their epistemological value when analyzing middle school education from a social perspective. The categories described reveal systematic and structural principles with their own identity based on the social relations that people establish in each time and space. Methodology: The documentary review technique was used, which is useful to approach education from the social sphere and to distance oneself from the pedagogical component, which has generally been a research priority. Due to its sociological character, Bourdieu’s thought allows understanding the relationships built by teachers, students and parents in accordance with the incorporated habitus reflected through social practices that define actions and customs of school agents. Results and discussion: The research concludes that it is pertinent to think about education from different perspectives, precisely because it is a dynamic scenario subject to cultural and social changes depending on people’s interests. In this regard, it is observed that, from the reflection on educational trends, new discourses have been generated that enrich the theoretical-practical foundations built in the school environment. Conclusions: Education, as a social practice, expresses different perceptions of social and cultural life through the relationships that people build permanently.